2018
DOI: 10.1111/jphp.12983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medicines used to treat gastrointestinal diseases on the pharmacokinetics of coadministered drugs: a PEARRL Review

Abstract: Objectives Drugs used to treat gastrointestinal diseases (GI drugs) are widely used either as prescription or over-the-counter (OTC) medications and belong to both the 10 most prescribed and 10 most sold OTC medications worldwide. The objective of this review article is to discuss the most frequent interactions between GI and other drugs, including identification of the mechanisms behind these interactions, where possible.Key findings Current clinical practice shows that in many cases, these drugs are administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 300 publications
0
6
0
2
Order By: Relevance
“…As the dose of atropine increased, the area under the concentration-time curve (AUC) and the peak blood concentration of CyA decreased [25]. Drugs used to promote gastrointestinal motility can alter the pharmacokinetics of some coadministered drugs [26]. Fructus Aurantii flavonoids are one of the main components of Fructus Aurantii that possess prominent gastrointestinal motility promoting efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…As the dose of atropine increased, the area under the concentration-time curve (AUC) and the peak blood concentration of CyA decreased [25]. Drugs used to promote gastrointestinal motility can alter the pharmacokinetics of some coadministered drugs [26]. Fructus Aurantii flavonoids are one of the main components of Fructus Aurantii that possess prominent gastrointestinal motility promoting efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GI disease can affect colonic physiology and function, and in turn affect drug behaviour and performance in patients [40][41][42][43][44]. For example, colonic pH is known to be reduced in IBD patients; changes to the epithelium and its transporters occur in colorectal cancer; and numerous diseases alter colonic transit time [9,45,46].…”
Section: The Colonic Environmentmentioning
confidence: 99%
“…An extensive review focusing on the alteration of GI transit time by laxatives was provided by Litou et al 87…”
Section: Types Of Interactionsmentioning
confidence: 99%
“…An extensive review focusing on the alteration of GI transit time by laxatives was provided by Litou et al 87 Laxatives such as senna and bisacodyl have been reported to affect total and small intestinal transit times. Reduced GI transit time might affect the pharmacokinetics of coadministered drugs.…”
Section: Laxativesmentioning
confidence: 99%